Learning Excel 97 : advanced (ViaGrafix OklahomaUS, 1999)
Describes advanced features of Excel 97 including: creating custom formats; working in multiple worksheets; creating at template; protecting cells; and, demonstrating the text import wizard. A skill builder quiz is included with each chapter.
Located in the Learning Resource Centre